2019
DOI: 10.2196/15505
|View full text |Cite
|
Sign up to set email alerts
|

Telemonitoring of Crohn’s Disease and Ulcerative Colitis (TECCU): Cost-Effectiveness Analysis

Abstract: BackgroundAlthough electronic health interventions are considered safe and efficient, evidence regarding the cost-effectiveness of telemonitoring in inflammatory bowel disease is lacking.ObjectiveWe aimed to evaluate the cost-effectiveness and cost-utility of the Telemonitorización de la Enfermedad de Crohn y Colitis Ulcerosa (Telemonitoring of Crohn’s Disease and Ulcerative Colitis [TECCU]) Web platform (G_TECCU intervention group) for telemonitoring complex inflammatory bowel disease, compared with standard … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 44 publications
0
23
0
1
Order By: Relevance
“…It is not known whether the lack of close monitoring due to social distancing measures can lead, in the short- or long-term, to higher rates of clinical relapse or loss of response to therapy. In general, there is a need to restructure the IBD unit, use telemonitoring [ 34 , 35 ], or send questionnaires to the patients through emails, mobile communication applications, and text messaging to monitor their progress and detect adverse events that could be missed in those who are not under closer monitoring [ 36 ]. This is an important consideration during the COVID-19 outbreak: namely, to detect patients who need immediate medical attention and those who may postpone their appointments.…”
Section: Discussionmentioning
confidence: 99%
“…It is not known whether the lack of close monitoring due to social distancing measures can lead, in the short- or long-term, to higher rates of clinical relapse or loss of response to therapy. In general, there is a need to restructure the IBD unit, use telemonitoring [ 34 , 35 ], or send questionnaires to the patients through emails, mobile communication applications, and text messaging to monitor their progress and detect adverse events that could be missed in those who are not under closer monitoring [ 36 ]. This is an important consideration during the COVID-19 outbreak: namely, to detect patients who need immediate medical attention and those who may postpone their appointments.…”
Section: Discussionmentioning
confidence: 99%
“…One randomized controlled study conducted by de Jong et al [ 29 ] compared the cost-effectiveness of telemedicine and standard care for management of IBD; they found that telemedicine was safe and reduced outpatient visits and hospital admissions compared with standard care. Del Hoyo et al [ 30 ] suggested that compared with standard and telephone care, telemedicine with web-based programs decreased the direct and indirect costs for patients with IBD; other studies by Elkjaer [ 31 ] and de Jong [ 32 ] have shown similar results. Mao et al [ 33 ] mentioned that CCCF has organized a group of volunteer gastroenterologists that specialize in IBD to offer web-based consultancy to patients with IBD.…”
Section: Discussionmentioning
confidence: 94%
“…In the field of gastroenterology, there are numerous application scenarios for telemedical care concepts, such as general digestive disease management programs[ 53 ]. Other telemedical tools are offered for IBD[ 54 , 55 ], CLDs[ 6 ], liver transplant patients[ 56 ] or diabetes patients[ 57 ]. In a literature review from Serper et al[ 6 ], the authors illustrated different uses for telemedicine in CLDs.…”
Section: Opportunitiesmentioning
confidence: 99%